Cold Water Immersion Offers No Functional or Perceptual Benefit Compared to a Sham Intervention During a Resistance Training Program. Issue 10 (28th October 2021) - Wilson, Laura J.; Dimitriou, Lygeri; Hills, Frank A.; Gondek, Marcela B.; van Wyk, Aléchia; Turek, Vlad; Rivkin, Taylor; Villiere, Alex; Jarvis, Paul; Miller, Stuart; Turner, Anthony; Cockburn, Emma
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Wilson, LJ, Dimitriou, L, Hills, FA, Gondek, MB, van Wyk, A, Turek, V, Rivkin, T, Villiere, A, Jarvis, P, Miller, S, Turner, A, and Cockburn, E. Cold water immersion offers no functional or perceptual benefit compared to a sham intervention during a resistance training program. J Strength Cond Res 35(10): 2720–2727, 2021—Cold water immersion (CWI) is regularly used by athletes as a postexercise recovery strategy, but relatively little is understood about potential training adaptations associated with habitual use. The aim of this study was to investigate the influence of repeated CWI or a sham intervention on adaptations to a lower body resistance training program. Thirteen men (26 ± 6 years; 83.6 ± 15.7 kg) familiar with resistance training were allocated into a CWI (10 minutes at 10° C) or sham group and completed 2 × 4-week blocks of lower body resistance training. Subjects completed a total of 16 training sessions (2 × session·week −1 ), with each session immediately followed by their allocated recovery intervention. Measures of perceptual markers, muscle function, and muscle architecture were recorded at baseline, midpoint, and post-training. Data were analyzed using factorial analysis of variances. The training program resulted in significant increases in muscle fibre pennation angle ( p = 0.009), isometric peak force ( p = 0.018), and 1/4 squat ( p < 0.001) with no differences between groups (all p > 0.05). There were no differences in perceptual responses between groups. Despite the popularity of CWI as a postexercise recovery intervention, the findings from the present study demonstrated no functional or perceptual benefit compared with a sham intervention during progressive strength and power training. Furthermore, there was no detrimental impact of CWI on morphological adaptations after 16 exposures. These findings are important for athletes and practitioners wishing to use CWI as an acute recovery strategy after training, without blunting potential training adaptations.